التفكيـر التنسيقي عند المتفوقين دراسيا من تلاميذ السنة الرابعة متوسط - زواري أحمد, خليفة; منصر, نادية (جامعة الوادي - University of Eloued, 2021)
تهدف الدراسة إلى الكشف عن مستوى التفكير التنسيقى لدى المتفوقين دراسيا من تلاميذ السنة الرابعة متوسط، ولتحقيق أهداف الدراسة، تم استخدام المنهج الوصفي الاستكشافي، وتطبيق مقياس التفكير التنسيقي لـرفعت محمود بهجات وآخرون(2012)، على عينة تعدادها 100 تلميذ تم اختيارهم بطريقة عشوائية من بعض متوسطات دائرة البياضة الوادي، بناء على معدل تحصيلهم الدراسي. وأسفرت نتائج الدراسة إلى أن أغلبية التلاميذ المتفوقين دراسيا المتمدرسين بالسنة الرابعة متوسط يتميزون بمستوى منخفض على مقياس التفكير التنسيقي وأبعاده: (التباعدي، التحليلي، التركيبي، النسقي، العلمي، الناقد). Abstract: This study aims to reveal the level of coordination thinking among a sample of 100 high- achieving fourth year middle school students. A descriptive method was applied using the coordination thinking scale of Refaat Mahmoud Bahgat and others (2012). The students were randomly selected on the basis of their academic achievement scores from middle schools at the Al-Bayada department of El oued. The findings of the of the study showed a low level of coordination thinking according to their overall score on the coordination thinking scale as well as on the different dimensions of the scale:(divergent, analytical, synthetic, systemic, scientific, critical).
مقال
Keywords: التفكير التنسيقي؛ التفوق الدراسي؛ التحصيل الدراسي; coordination thinking; Academic excellence, high-achieving students